Assessing Chinese English Majors' Intercultural Skills From Teachers' Perspective - Jingjing, Zhou; Florence, Gilliam Kayad; Vimala, Govindaraju (Asian Scholars Network (ASNet), 2024)
Most previous studies have used student self-reported data to investigate their proficiency in intercultural skills, while few have examined it from teacher’s perspective. This paper reports a qualitative case study on English major students’ intercultural skills in Chinese higher education. The instrument was adapted from the scale of Intercultural Ability developed by Fantini (2007). The data were collected from in-depth interview from 8 English major teachers and analyzed by thematic analysis. The findings indicated that students’ intercultural skills proficiency were limited as they (1) unable to fully express themselves, (2) unable to accurately express Chinese culture, (3) able to communicate in a limited manner, and (4) unable to deal with culture conflicts flexibly. Keywords: Students’ Intercultural Skills, Teacher Perception, Higher Education In China